(untitled) (Architecture Image Studies, 2026)
This study analyzes media coverage of the student demonstrations in Makassar known as the Demonstrasi Peringatan Darurat (Emergency Commemoration Demonstration), one of the largest protest movements in Indonesia in the post–New Order era. The analysis employs a critical discourse analysis framework based on Theo van Leeuwen’s model of exclusion and inclusion. The main focus of this study is to reveal how the media outlet Rakyat Sulsel frames the news by prioritizing exclusion strategies that marginalize anarchist groups and obscure police responsibility for the violence that occurred. The exclusion strategy consists of three sub-strategies, while the inclusion strategy comprises seven. This study finds that the use of language and media representation contributes to the social construction of the identity of anarchist groups. Thus, media discourse does not merely convey information but also shapes narratives that can influence public perceptions and/or reinforce stigma toward anarchist groups and anarchism as an ideology. The findings highlight the importance of the media’s role as an ideological apparatus that has the potential to reinforce the status quo while neglecting alternative voices within society. This study is expected to encourage a more critical understanding of media coverage and to raise awareness of possible biases in news reporting.